Evaluasi Kebijakan Pelayanan SIPRAJA: Studi Kasus di Desa Damarsi, Kabupaten Sidoarjo - Pesica Kristanto, Catharina Irene; Nawangsari, Ertien Rining (Jurnal Noken: Ilmu-Ilmu Sosial, 2024)
The utilization of e-government has been mandated by the Sidoarjo District Government through the introduction of android-based and website-based public service innovations known as SIPRAJA. This service is expected to address the fundamental needs of the Sidoarjo community, providing a faster, easier, more affordable, and satisfying process. This research aims to evaluate the policy of SIPRAJA in public services in Damarsi Village, Buduran Sub-district, Sidoarjo District. The study employs a qualitative descriptive approach, utilizing data collection techniques such as interviews, observations, documentation, and online data tracking. Data analysis involves collecting, condensing, presenting, drawing conclusions, and verifying data. The research findings indicate that in terms of effectiveness, there has been a decrease in SIPRAJA usage due to technical constraints such as system delays, registration issues, and limitations in technology use, preventing optimal effectiveness. Efficiency in population administration management appears successful due to minimal efforts required from village officials and the community. Even distribution is declared successful because there is uniform distribution of access, services, costs, and benefits. Responsiveness in SIPRAJA implementation appears successful due to its responsive service with positive interaction between officials and the community. Accuracy is declared successful but requires further adjustments and improvements. Keywords: Policy Evaluation, Public Services, Sidoarjo People's Service System (SIPRAJA)